Undergraduate Gender Diversity and the Direction of Scientific Research - Truffa, Francesca; Wong, Ashley (American Economic Review, 2025)
Can diversity lead to greater research focus on populations underrepresented in science? Between 1960 and 1990, 76 all-male US universities transitioned to coeducation. Using a generalized difference-in-differences design, we find that coeducation led to a 44 percent increase in gender-related research publications. This increase is driven by research focused on female subjects and gender differences. While coeducation led to a compositional shift with more women and researchers interested in gender topics, much of the increase comes from male incumbent researchers shifting their research focus toward gender-related topics. The results support interaction with more diverse students and peers as key underlying mechanisms. (JEL I23, J16, O31, O34)